2-Azabicyclo[2.2.1]hept-5-enes from 7-azabicyclo[2.2.1]heptadienes by tandem intermolecular radical addition-homoallylic radical rearrangement - Hodgson, D; Bebbington, M; Willis, P (2001)
Addition of thiols to 7-azabicyclo[2.2.1]heptadienes such as 16 leads exclusively to 7-thio-substituted 2-azabicyclo[2.2.1]hept-5-enes 17 in good yields via tandem intermolecular radical addition - homoallylic radical rearrangement.